(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The investigation of floristic composition and vegetation of Astvatsatsin mountain revealed 250 species from 117 genera and 37 families. Identification of flora showed that the most common species belong to plant from the following families: Asteraceae, Poaceae, Fabaceae, Caryophyllaceae and Brassicacea. It has been established that the investigated area is represented by frigana, steppe, meadow and petrofits.